Advanced methods in materials processing defects - Predeleanu, M.; Gilormini, P. (Studies in applied mechanics, 1997)
This collection of papers focus on advanced methods for predicting and avoiding the occurrence of defects in manufactured products. A new feature is included, namely, the influence of the processing-induced defects on the integrity of structures. The following topics are developed: damage modeling; damage evaluation and rupture; strain localization and instability analysis; formability characterization; prediction of shape inaccuracies; influence of defects on structural integrity. The main manufacturing operations are covered and various materials are examined, such as new and conventional metal alloys, ceramics, polymers and composites.